Synovial mesenchymal stem cell-derived extracellular vesicles alleviate chondrocyte damage during osteoarthritis through microRNA-130b-3p-mediated inhibition of the LRP12/AKT/β-catenin axis. (4th March 2022) - Zeng, Zhenhua; Dai, Yi; Deng, Shuo; Zou, Sanbao; Dou, Tingyang; Wei, Feng
Abstract: Background: Synovial mesenchymal stem cells (SMSCs) have been discussed as promising tools for protecting chondrocytes from loss and inhibiting osteoarthritis (OA). This work infocuses on the function of SMSC-derived extracellular vesicles (EVs) in chondrocytes during OA and the molecular mechanism. Methods: EVs were extracted from SMSCs and identified. Chondrocytes were treated with interleukin (IL)-1β to induce an OA-like condition in vitro and then treated with EVs. The proliferation, apoptosis, migration, extracellular matrix (ECM) degradation and inflammation in chondrocytes were examined. Key microRNAs (miRNAs) carried by EVs were screened using a microarray analysis, and the downstream molecules involved were explored using bioinformatic analysis. Rescue experiments were performed to validate the involvements of these molecules in EV-mediated events. Results: EVs restored proliferation and migration while reduced apoptosis, ECM degradation and the secretion of pro-inflammatory cytokines in chondrocytes induced by IL-1β. miR-130b-3p was significantly elevated in chondrocytes after EVs treatment. Knockdown of miR-130b-3p blocked the protective roles of EVs against IL-1β-induced damage to chondrocytes. miR-130b-3p was found to target LDL receptor related protein 12 (LRP12) mRNA in chondrocytes. Overexpression of LRP12 counteracted the effects of EVs as well and activated the AKT/β-catenin signaling pathway. Conclusion: This study provided evidence that EVs alleviate chondrocyte damage during OA through miR-130b-3p-mediated inhibition of the LRP12/AKT/β-catenin axis. This study may offer novel thoughts into the protection of chondrocytes and the management of OA.